Emissivity of metal surface coatings - Lanc, Zorana; Zeljković, Milan; Hadžistević, Miodrag; Štrbac, Branko; Labus Zlatanović, Danka; Baloš, Sebastian (Journal of Production Engineering, 2022)
As it is known, emissivity is paramount for accurate temperature measurement using IR thermography. The emissivity of metals is particularly interesting due to its variability in relation to surface conditions (surface roughness and oxidation state), viewing angle, temperature, and wavelength. In the frame of this paper, knowledge regarding metal surface coatings and its effect on emissivity has been gained in an effort to improve risk assessment of workplace burns arising from hot metal surfaces. The present study examined the emissivity of two component polyurethane metal covering coat on steel and grey cast iron depending on temperature and coating thickness. It was concluded that metal coating leads to moderated metal heating and increases constancy of emissivity compared to uncoated metal surfaces.